Neurological diseases in the aborigines of Ancient Perú - Paico-Vílchez, Emiliano (2023)
In this article, the authors describe some historical data that demonstrate the existence of neurological diseases suffered by the aborigines of Ancient Peru. They also explain the methods they used in the treatment of these diseases.